Interpolation par des fonctions entières: Interpolation by entire functions - Groza, Ghiocel; Pop, Nicolae (Rev. Anal. Numér. Théor. Approx., 2006)
In French.Soit \(A\) une algèbre normè unifère commutative complète sur un corps commutatif à valeur absolue non triviale. L'article montre qu'il existe une fonction entière, ayant les coefficients en \(A\) qui donne une solution pour un problème d'interpolation infinie en \(A\).In English.Let \(A\) be a complete commutative uniferous norm algebra over a nontrivial absolute value commutative field. The article shows that there exists an integer function, having the coefficients in \(A\) that gives a solution for an infinite interpolation problem in \(A\).